STUDY OF THE INFLUENCE OF FACTORS ON THE CONTENT OF RUSSIAN FEDERAL CHANNELS IN THE CONTEXT OF DIGITALIZATION - A. R. Akopyan; A. M. Arakelyan; Yu. V. Vorontsova; V. V. Krysov (Вестник университета)
The authors carry out a study of the influence of various factors on the content of Russian federal channels. Using content analysis of the broadcast data were obtained to identify the influence of factors, characteristic for the stage of formation of a consumer society in Russia on the content of television channels and the analysis of conformity of telecasts the authors developed, criteria that have been formed and considered together with current trends in society related to the digitalization processes, and preferences of Russians. Television is an important social institution that should not only reflect the current situation in society, but also broadcast certain behaviors, culture and values. Television content requires a lot of attention, because now there are significant changes in the individual in the new conditions of digital communication. Modern television content should move away from the simple model of mass culture, which is based on a standardized approach based on entertainment content. Content should take into account modern consumer values.